2020
DOI: 10.3390/healthcare8030321
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Retirees: A Meta-Analysis

Abstract: Background: Retirement is a final life stage characterized by the ceasing of work and the loss of a routine, social relations, role, status, accomplishments, and aspirations, etc. Many times it is accompanied by negative feelings and can provoke different psychoemotional reactions such as depression, among others. The aim of this study is to analyze the prevalence of depression, as well as its psychoeducational approach in retirees. Methods: A paired systematic review with meta-analysis was conducted in differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 26 publications
3
12
0
1
Order By: Relevance
“…These findings confirm the conclusions in Bassanini and Caroli (2015), who showed that being forced to work while preferring to retire and, symmetrically, being forced to stop working because of workers have no control on the retirement and work decisions have a health damaging effect. Similar results are provided by Pabón-Carrasco et al (2020) and Li et al (2021), but limited to the effects on depressive symptoms. Moreover, the negative impact of postponed retirement on health, compared to statutory retirement, could reflect the consequences of being stuck in employment while one had planned to retire, for example due to pension reforms which increase the retirement age or the length of the contribution period required to be entitled to pension (see e.g.…”
Section: Multivariate Meta-regressionssupporting
confidence: 87%
See 2 more Smart Citations
“…These findings confirm the conclusions in Bassanini and Caroli (2015), who showed that being forced to work while preferring to retire and, symmetrically, being forced to stop working because of workers have no control on the retirement and work decisions have a health damaging effect. Similar results are provided by Pabón-Carrasco et al (2020) and Li et al (2021), but limited to the effects on depressive symptoms. Moreover, the negative impact of postponed retirement on health, compared to statutory retirement, could reflect the consequences of being stuck in employment while one had planned to retire, for example due to pension reforms which increase the retirement age or the length of the contribution period required to be entitled to pension (see e.g.…”
Section: Multivariate Meta-regressionssupporting
confidence: 87%
“…people in the group of those who work beyond the standard retirement age are on average healthier than those who retire on-time. Finally, both Pabón-Carrasco et al (2020) and Li et al (2021) only focus on depressive symptoms: 2 according to the former, the retirees with the highest prevalence of depression are those ones who retire in a mandatory fashion or due to illness; the latter show that the association of involuntary retirement with more depressive symptoms is stronger than voluntary or regulatory retirement, and it is more pronounced in Eastern developed countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depression is more common in retirees, with compulsory pensions, ill pensions, and anticipated retirement showing higher disease rates. Pabón-Carrasco et al (2020) discovered that nearly a third of retirees suffer from depression; it is necessary to take precautions and early detection to approach public health problems. Unexpected medical bills in terms of health care are a significant concern for many retirees.…”
Section: Healthcarementioning
confidence: 99%
“…In some countries, workers are required to retire at a specified age; 7 even in areas without a mandatory retirement age, most older adults retire from the workforce. 8 Prevalence of depression among retirees was estimated at 28%, 9 substantially higher than that of the overall older adult population. Retirement is a multi-faceted event (eg, timing, expectedness, voluntariness), and understanding how these various elements intersect with mental health has implications for addressing depression prior to, during, and after this transition.…”
Section: Introductionmentioning
confidence: 99%